A cross-sectional study determining prevalence and factors associated with ST-segment elevation myocardial infarction and non-ST segment elevation myocardial infarction in Iran: results from fasa registry on acute myocardial infarction (FaRMI) - Mehdi Sharafi; Azizallah Dehghan; Ali Mouseli; Hossein Fatemian; Leila Jamali; Sima Afrashteh; Mahsa Rostami Chijan; Zahra Mastaneh; Abdoljabbar Zakeri; Abdulhakim Alkamel (BMC, 2024)
Abstract Background Acute myocardial infarction is still a leading cause of death worldwide, accounting for roughly three million deaths yearly. This study aimed to investigate the prevalence and factors associated with ST-Segment Elevation Myocardial Infarction and Non-ST Segment Elevation Myocardial Infarction in Iran. Methods This cross-sectional study was conducted using the databases of the Fasa Registry on Acute Myocardial Infarction (FaRMI) and the Fasa Adult Cohort Study (FACS). chi-squared and one-way ANOVA tests were utilized to calculate the unadjusted associations between the study variables. A multivariate multinomial logistic regression model was also employed to determine the adjusted association of each independent variable with the risk of ST-elevation myocardial infarction (STEMI). Results The prevalence of STEMI and non-STEMI was 31.60% and 11.80%, respectively. Multinomial logistic regression showed that older age, anemia, high WBC, and high creatinine levels were associated with higher odds of STEMI and non-STEMI compared to healthy individuals. In addition, based on the analysis being a woman(OR = 0.63,95%CI:0.51-0.78), anemia(OR = 0.67,95%CI:0.54-0.63)and hypertension (OR = 0.80,95%CI:0.65-0.97)decreased the likelihood of STEMI occurrence compared to non-STEMI, while high WBC(OR = 1.19,95%CI:1.15-1.23)increased the odds. Conclusion In this study, significant predictors of MI risk included age, gender, anemia, lipid profile, inflammation, and renal function. Subsequent investigations ought to prioritize the comprehensive understanding of the underlying mechanisms that drive these connections and assess the effectiveness of specific interventions aimed at diminishing the occurrence of MI and improving patient outcomes.